Algebraic and Analytic Methods - 1.6 Vectors and Vector-Valued Functions

From testwiki
Revision as of 10:59, 28 June 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision β†’ (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
1.6#Ex1 𝐚 = ( a 1 , a 2 , a 3 ) 𝐚 subscript π‘Ž 1 subscript π‘Ž 2 subscript π‘Ž 3 {\displaystyle{\displaystyle\mathbf{a}=(a_{1},a_{2},a_{3})}}
\mathbf{a} = (a_{1},a_{2},a_{3})

a = (a[1], a[2], a[3])
a == (Subscript[a, 1], Subscript[a, 2], Subscript[a, 3])
Skipped - no semantic math Skipped - no semantic math - -
1.6#Ex2 𝐛 = ( b 1 , b 2 , b 3 ) 𝐛 subscript 𝑏 1 subscript 𝑏 2 subscript 𝑏 3 {\displaystyle{\displaystyle\mathbf{b}=(b_{1},b_{2},b_{3})}}
\mathbf{b} = (b_{1},b_{2},b_{3})

b = (b[1], b[2], b[3])
b == (Subscript[b, 1], Subscript[b, 2], Subscript[b, 3])
Skipped - no semantic math Skipped - no semantic math - -
1.6.E2 𝐚 β‹… 𝐛 = a 1 ⁒ b 1 + a 2 ⁒ b 2 + a 3 ⁒ b 3 β‹… 𝐚 𝐛 subscript π‘Ž 1 subscript 𝑏 1 subscript π‘Ž 2 subscript 𝑏 2 subscript π‘Ž 3 subscript 𝑏 3 {\displaystyle{\displaystyle\mathbf{a}\cdot\mathbf{b}=a_{1}b_{1}+a_{2}b_{2}+a_% {3}b_{3}}}
\mathbf{a}\cdot\mathbf{b} = a_{1}b_{1}+a_{2}b_{2}+a_{3}b_{3}

a * b = a[1]*b[1]+ a[2]*b[2]+ a[3]*b[3]
a * b == Subscript[a, 1]*Subscript[b, 1]+ Subscript[a, 2]*Subscript[b, 2]+ Subscript[a, 3]*Subscript[b, 3]
Skipped - no semantic math Skipped - no semantic math - -
1.6.E3 βˆ₯ 𝐚 βˆ₯ = 𝐚 β‹… 𝐚 norm 𝐚 β‹… 𝐚 𝐚 {\displaystyle{\displaystyle\|\mathbf{a}\|=\sqrt{\mathbf{a}\cdot\mathbf{a}}}}
\|\mathbf{a}\| = \sqrt{\mathbf{a}\cdot\mathbf{a}}

Error
Norm[a] == Sqrt[a * a]
Skipped - no semantic math Skipped - no semantic math - -
1.6.E4 cos ⁑ ΞΈ = 𝐚 β‹… 𝐛 βˆ₯ 𝐚 βˆ₯ ⁒ βˆ₯ 𝐛 βˆ₯ πœƒ β‹… 𝐚 𝐛 norm 𝐚 norm 𝐛 {\displaystyle{\displaystyle\cos\theta=\frac{\mathbf{a}\cdot\mathbf{b}}{\|% \mathbf{a}\|\;\|\mathbf{b}\|}}}
\cos@@{\theta} = \frac{\mathbf{a}\cdot\mathbf{b}}{\|\mathbf{a}\|\;\|\mathbf{b}\|}

Error
Cos[\[Theta]] == Divide[a * b,Norm[a]*Norm[b]]
Failure Failure
Failed [300 / 300]
Result: -.2694569811-.3969495503*I
Test Values: {a = -1.5, b = -1.5, theta = 1/2*3^(1/2)+1/2*I}

Result: .227765517+.4690753764*I
Test Values: {a = -1.5, b = -1.5, theta = -1/2+1/2*I*3^(1/2)}

Result: .227765517+.4690753764*I
Test Values: {a = -1.5, b = -1.5, theta = 1/2-1/2*I*3^(1/2)}

Result: -.2694569811-.3969495503*I
Test Values: {a = -1.5, b = -1.5, theta = -1/2*3^(1/2)-1/2*I}

... skip entries to safe data
Failed [300 / 300]
Result: Complex[-0.2694569809427748, -0.3969495502290325]
Test Values: {Rule[a, -1.5], Rule[b, -1.5], Rule[ΞΈ, Power[E, Times[Complex[0, Rational[1, 6]], Pi]]]}

Result: Complex[0.2277655168641104, 0.46907537626850365]
Test Values: {Rule[a, -1.5], Rule[b, -1.5], Rule[ΞΈ, Power[E, Times[Complex[0, Rational[2, 3]], Pi]]]}

... skip entries to safe data
1.6.E6 𝐚 = a 1 ⁒ 𝐒 + a 2 ⁒ 𝐣 + a 3 ⁒ 𝐀 𝐚 subscript π‘Ž 1 𝐒 subscript π‘Ž 2 𝐣 subscript π‘Ž 3 𝐀 {\displaystyle{\displaystyle\mathbf{a}=a_{1}\mathbf{i}+a_{2}\mathbf{j}+a_{3}% \mathbf{k}}}
\mathbf{a} = a_{1}\mathbf{i}+a_{2}\mathbf{j}+a_{3}\mathbf{k}

a = a[1]*i + a[2]*j + a[3]*((0 , 0 , 1))
a == Subscript[a, 1]*i + Subscript[a, 2]*j + Subscript[a, 3]*((0 , 0 , 1))
Skipped - no semantic math Skipped - no semantic math - -
1.6#Ex6 𝐒 Γ— 𝐣 = 𝐀 𝐒 𝐣 𝐀 {\displaystyle{\displaystyle\mathbf{i}\times\mathbf{j}=\mathbf{k}}}
\mathbf{i}\times\mathbf{j} = \mathbf{k}

i * j = ((0 , 0 , 1))
i * j == ((0 , 0 , 1))
Skipped - no semantic math Skipped - no semantic math - -
1.6#Ex7 𝐣 Γ— 𝐀 = 𝐒 𝐣 𝐀 𝐒 {\displaystyle{\displaystyle\mathbf{j}\times\mathbf{k}=\mathbf{i}}}
\mathbf{j}\times\mathbf{k} = \mathbf{i}

j *((0 , 0 , 1)) = i
j *((0 , 0 , 1)) == i
Skipped - no semantic math Skipped - no semantic math - -
1.6#Ex8 𝐀 Γ— 𝐒 = 𝐣 𝐀 𝐒 𝐣 {\displaystyle{\displaystyle\mathbf{k}\times\mathbf{i}=\mathbf{j}}}
\mathbf{k}\times\mathbf{i} = \mathbf{j}

((0 , 0 , 1)) * i = j
((0 , 0 , 1)) * i == j
Skipped - no semantic math Skipped - no semantic math - -
1.6#Ex9 𝐣 Γ— 𝐒 = - 𝐀 𝐣 𝐒 𝐀 {\displaystyle{\displaystyle\mathbf{j}\times\mathbf{i}=-\mathbf{k}}}
\mathbf{j}\times\mathbf{i} = -\mathbf{k}

j * i = -((0 , 0 , 1))
j * i == -((0 , 0 , 1))
Skipped - no semantic math Skipped - no semantic math - -
1.6#Ex10 𝐀 Γ— 𝐣 = - 𝐒 𝐀 𝐣 𝐒 {\displaystyle{\displaystyle\mathbf{k}\times\mathbf{j}=-\mathbf{i}}}
\mathbf{k}\times\mathbf{j} = -\mathbf{i}

((0 , 0 , 1)) * j = - i
((0 , 0 , 1)) * j == - i
Skipped - no semantic math Skipped - no semantic math - -
1.6#Ex11 𝐒 Γ— 𝐀 = - 𝐣 𝐒 𝐀 𝐣 {\displaystyle{\displaystyle\mathbf{i}\times\mathbf{k}=-\mathbf{j}}}
\mathbf{i}\times\mathbf{k} = -\mathbf{j}

i *((0 , 0 , 1)) = - j
i *((0 , 0 , 1)) == - j
Skipped - no semantic math Skipped - no semantic math - -
1.6.E12 a j ⁒ b j = βˆ‘ j = 1 3 a j ⁒ b j subscript π‘Ž 𝑗 subscript 𝑏 𝑗 superscript subscript 𝑗 1 3 subscript π‘Ž 𝑗 subscript 𝑏 𝑗 {\displaystyle{\displaystyle a_{j}b_{j}=\sum_{j=1}^{3}a_{j}b_{j}}}
a_{j}b_{j} = \sum_{j=1}^{3}a_{j}b_{j}

a[j]*b[j] = sum(a[j]*b[j], j = 1..3)
Subscript[a, j]*Subscript[b, j] == Sum[Subscript[a, j]*Subscript[b, j], {j, 1, 3}, GenerateConditions->None]
Skipped - no semantic math Skipped - no semantic math - -
1.6#Ex15 ϡ 1 ⁣ 2 ⁣ 3 = ϡ 3 ⁣ 1 ⁣ 2 Levi-Civita 1 2 3 Levi-Civita 3 1 2 {\displaystyle{\displaystyle\epsilon_{123}=\epsilon_{312}}}
\LeviCivitasym{1}{2}{3} = \LeviCivitasym{3}{1}{2}

LeviCivita[1, 2, 3] = LeviCivita[3, 1, 2]
Part[LeviCivitaTensor[3,List], 1, 2, 3] == Part[LeviCivitaTensor[3,List], 3, 1, 2]
Successful Successful - Successful [Tested: 1]
1.6#Ex15 ϡ 3 ⁣ 1 ⁣ 2 = 1 Levi-Civita 3 1 2 1 {\displaystyle{\displaystyle\epsilon_{312}=1}}
\LeviCivitasym{3}{1}{2} = 1

LeviCivita[3, 1, 2] = 1
Part[LeviCivitaTensor[3,List], 3, 1, 2] == 1
Successful Successful - Successful [Tested: 1]
1.6#Ex16 ϡ 2 ⁣ 1 ⁣ 3 = ϡ 3 ⁣ 2 ⁣ 1 Levi-Civita 2 1 3 Levi-Civita 3 2 1 {\displaystyle{\displaystyle\epsilon_{213}=\epsilon_{321}}}
\LeviCivitasym{2}{1}{3} = \LeviCivitasym{3}{2}{1}

LeviCivita[2, 1, 3] = LeviCivita[3, 2, 1]
Part[LeviCivitaTensor[3,List], 2, 1, 3] == Part[LeviCivitaTensor[3,List], 3, 2, 1]
Successful Successful - Successful [Tested: 1]
1.6#Ex16 ϡ 3 ⁣ 2 ⁣ 1 = - 1 Levi-Civita 3 2 1 1 {\displaystyle{\displaystyle\epsilon_{321}=-1}}
\LeviCivitasym{3}{2}{1} = -1

LeviCivita[3, 2, 1] = - 1
Part[LeviCivitaTensor[3,List], 3, 2, 1] == - 1
Successful Successful - Successful [Tested: 1]
1.6#Ex17 ϡ 2 ⁣ 2 ⁣ 1 = 0 Levi-Civita 2 2 1 0 {\displaystyle{\displaystyle\epsilon_{221}=0}}
\LeviCivitasym{2}{2}{1} = 0

LeviCivita[2, 2, 1] = 0
Part[LeviCivitaTensor[3,List], 2, 2, 1] == 0
Successful Successful - Successful [Tested: 1]
1.6.E16 Ο΅ j ⁣ k ⁣ β„“ ⁒ Ο΅ β„“ ⁣ m ⁣ n = Ξ΄ j , m ⁒ Ξ΄ k , n - Ξ΄ j , n ⁒ Ξ΄ k , m Levi-Civita 𝑗 π‘˜ β„“ Levi-Civita β„“ π‘š 𝑛 Kronecker 𝑗 π‘š Kronecker π‘˜ 𝑛 Kronecker 𝑗 𝑛 Kronecker π‘˜ π‘š {\displaystyle{\displaystyle\epsilon_{jk\ell}\epsilon_{\ell mn}=\delta_{j,m}% \delta_{k,n}-\delta_{j,n}\delta_{k,m}}}
\LeviCivitasym{j}{k}{\ell}\LeviCivitasym{\ell}{m}{n} = \Kroneckerdelta{j}{m}\Kroneckerdelta{k}{n}-\Kroneckerdelta{j}{n}\Kroneckerdelta{k}{m}

LeviCivita[j, k, ell]*LeviCivita[ell, m, n] = KroneckerDelta[j, m]*KroneckerDelta[k, n]- KroneckerDelta[j, n]*KroneckerDelta[k, m]
Part[LeviCivitaTensor[3,List], j, k, \[ScriptL]]*Part[LeviCivitaTensor[3,List], \[ScriptL], m, n] == KroneckerDelta[j, m]*KroneckerDelta[k, n]- KroneckerDelta[j, n]*KroneckerDelta[k, m]
Failure Failure Error Error
1.6.E17 𝐞 j Γ— 𝐞 k = Ο΅ j ⁣ k ⁣ β„“ ⁒ 𝐞 β„“ subscript 𝐞 𝑗 subscript 𝐞 π‘˜ Levi-Civita 𝑗 π‘˜ β„“ subscript 𝐞 β„“ {\displaystyle{\displaystyle\mathbf{e}_{j}\times\mathbf{e}_{k}=\epsilon_{jk% \ell}\mathbf{e}_{\ell}}}
\mathbf{e}_{j}\times\mathbf{e}_{k} = \LeviCivitasym{j}{k}{\ell}\mathbf{e}_{\ell}

e[j] * e[k] = LeviCivita[j, k, ell]*e[ell]
Subscript[e, j] * Subscript[e, k] == Part[LeviCivitaTensor[3,List], j, k, \[ScriptL]]*Subscript[e, \[ScriptL]]
Translation Error Translation Error - -
1.6.E18 a j ⁒ 𝐞 j Γ— b k ⁒ 𝐞 k = Ο΅ j ⁣ k ⁣ β„“ ⁒ a j ⁒ b k ⁒ 𝐞 β„“ subscript π‘Ž 𝑗 subscript 𝐞 𝑗 subscript 𝑏 π‘˜ subscript 𝐞 π‘˜ Levi-Civita 𝑗 π‘˜ β„“ subscript π‘Ž 𝑗 subscript 𝑏 π‘˜ subscript 𝐞 β„“ {\displaystyle{\displaystyle a_{j}\mathbf{e}_{j}\times b_{k}\mathbf{e}_{k}=% \epsilon_{jk\ell}a_{j}b_{k}\mathbf{e}_{\ell}}}
a_{j}\mathbf{e}_{j}\times b_{k}\mathbf{e}_{k} = \LeviCivitasym{j}{k}{\ell}a_{j}b_{k}\mathbf{e}_{\ell}

a[j]*e[j] * b[k]*e[k] = LeviCivita[j, k, ell]*a[j]*b[k]*e[ell]
Subscript[a, j]*Subscript[e, j] * Subscript[b, k]*Subscript[e, k] == Part[LeviCivitaTensor[3,List], j, k, \[ScriptL]]*Subscript[a, j]*Subscript[b, k]*Subscript[e, \[ScriptL]]
Translation Error Translation Error - -
1.6.E43 𝐅 ⁒ ( x , y ) = F 1 ⁒ ( x , y ) ⁒ 𝐒 + F 2 ⁒ ( x , y ) ⁒ 𝐣 𝐅 π‘₯ 𝑦 subscript 𝐹 1 π‘₯ 𝑦 𝐒 subscript 𝐹 2 π‘₯ 𝑦 𝐣 {\displaystyle{\displaystyle\mathbf{F}(x,y)=F_{1}(x,y)\mathbf{i}+F_{2}(x,y)% \mathbf{j}}}
\mathbf{F}(x,y) = F_{1}(x,y)\mathbf{i}+F_{2}(x,y)\mathbf{j}

F(x , y) = F[1](x , y)* i + F[2](x , y)* j
F[x , y] == Subscript[F, 1][x , y]* i + Subscript[F, 2][x , y]* j
Skipped - no semantic math Skipped - no semantic math - -
1.6.E46 𝐓 u = βˆ‚ ⁑ x βˆ‚ ⁑ u ⁒ ( u 0 , v 0 ) ⁒ 𝐒 + βˆ‚ ⁑ y βˆ‚ ⁑ u ⁒ ( u 0 , v 0 ) ⁒ 𝐣 + βˆ‚ ⁑ z βˆ‚ ⁑ u ⁒ ( u 0 , v 0 ) ⁒ 𝐀 subscript 𝐓 𝑒 partial-derivative π‘₯ 𝑒 subscript 𝑒 0 subscript 𝑣 0 𝐒 partial-derivative 𝑦 𝑒 subscript 𝑒 0 subscript 𝑣 0 𝐣 partial-derivative 𝑧 𝑒 subscript 𝑒 0 subscript 𝑣 0 𝐀 {\displaystyle{\displaystyle\mathbf{T}_{u}=\frac{\partial x}{\partial u}(u_{0}% ,v_{0})\mathbf{i}+\frac{\partial y}{\partial u}(u_{0},v_{0})\mathbf{j}+\frac{% \partial z}{\partial u}(u_{0},v_{0})\mathbf{k}}}
\mathbf{T}_{u} = \pderiv{x}{u}(u_{0},v_{0})\mathbf{i}+\pderiv{y}{u}(u_{0},v_{0})\mathbf{j}+\pderiv{z}{u}(u_{0},v_{0})\mathbf{k}

T[u] = diff(x, u)*(u[0], v[0])*i + diff(y, u)*(u[0], v[0])*j + diff(x + y*I, u)*(u[0], v[0])*((0 , 0 , 1))
Subscript[T, u] == D[x, u]*(Subscript[u, 0], Subscript[v, 0])*i + D[y, u]*(Subscript[u, 0], Subscript[v, 0])*j + D[x + y*I, u]*(Subscript[u, 0], Subscript[v, 0])*((0 , 0 , 1))
Failure Failure
Failed [300 / 300]
Result: .8660254040+.5000000000*I
Test Values: {u = 1/2*3^(1/2)+1/2*I, x = 1.5, y = -1.5, T[u] = 1/2*3^(1/2)+1/2*I, u[0] = 1/2*3^(1/2)+1/2*I, v[0] = 1/2*3^(1/2)+1/2*I, j = 1, k = 1}

Result: .8660254040+.5000000000*I
Test Values: {u = 1/2*3^(1/2)+1/2*I, x = 1.5, y = -1.5, T[u] = 1/2*3^(1/2)+1/2*I, u[0] = 1/2*3^(1/2)+1/2*I, v[0] = 1/2*3^(1/2)+1/2*I, j = 1, k = 2}

Result: .8660254040+.5000000000*I
Test Values: {u = 1/2*3^(1/2)+1/2*I, x = 1.5, y = -1.5, T[u] = 1/2*3^(1/2)+1/2*I, u[0] = 1/2*3^(1/2)+1/2*I, v[0] = 1/2*3^(1/2)+1/2*I, j = 1, k = 3}

Result: .8660254040+.5000000000*I
Test Values: {u = 1/2*3^(1/2)+1/2*I, x = 1.5, y = -1.5, T[u] = 1/2*3^(1/2)+1/2*I, u[0] = 1/2*3^(1/2)+1/2*I, v[0] = 1/2*3^(1/2)+1/2*I, j = 2, k = 1}

... skip entries to safe data
-
1.6.E47 𝐓 v = βˆ‚ ⁑ x βˆ‚ ⁑ v ⁒ ( u 0 , v 0 ) ⁒ 𝐒 + βˆ‚ ⁑ y βˆ‚ ⁑ v ⁒ ( u 0 , v 0 ) ⁒ 𝐣 + βˆ‚ ⁑ z βˆ‚ ⁑ v ⁒ ( u 0 , v 0 ) ⁒ 𝐀 subscript 𝐓 𝑣 partial-derivative π‘₯ 𝑣 subscript 𝑒 0 subscript 𝑣 0 𝐒 partial-derivative 𝑦 𝑣 subscript 𝑒 0 subscript 𝑣 0 𝐣 partial-derivative 𝑧 𝑣 subscript 𝑒 0 subscript 𝑣 0 𝐀 {\displaystyle{\displaystyle\mathbf{T}_{v}=\frac{\partial x}{\partial v}(u_{0}% ,v_{0})\mathbf{i}+\frac{\partial y}{\partial v}(u_{0},v_{0})\mathbf{j}+\frac{% \partial z}{\partial v}(u_{0},v_{0})\mathbf{k}}}
\mathbf{T}_{v} = \pderiv{x}{v}(u_{0},v_{0})\mathbf{i}+\pderiv{y}{v}(u_{0},v_{0})\mathbf{j}+\pderiv{z}{v}(u_{0},v_{0})\mathbf{k}

T[v] = diff(x, v)*(u[0], v[0])*i + diff(y, v)*(u[0], v[0])*j + diff(x + y*I, v)*(u[0], v[0])*((0 , 0 , 1))
Subscript[T, v] == D[x, v]*(Subscript[u, 0], Subscript[v, 0])*i + D[y, v]*(Subscript[u, 0], Subscript[v, 0])*j + D[x + y*I, v]*(Subscript[u, 0], Subscript[v, 0])*((0 , 0 , 1))
Failure Failure
Failed [300 / 300]
Result: .8660254040+.5000000000*I
Test Values: {v = 1/2*3^(1/2)+1/2*I, x = 1.5, y = -1.5, T[v] = 1/2*3^(1/2)+1/2*I, u[0] = 1/2*3^(1/2)+1/2*I, v[0] = 1/2*3^(1/2)+1/2*I, j = 1, k = 1}

Result: .8660254040+.5000000000*I
Test Values: {v = 1/2*3^(1/2)+1/2*I, x = 1.5, y = -1.5, T[v] = 1/2*3^(1/2)+1/2*I, u[0] = 1/2*3^(1/2)+1/2*I, v[0] = 1/2*3^(1/2)+1/2*I, j = 1, k = 2}

Result: .8660254040+.5000000000*I
Test Values: {v = 1/2*3^(1/2)+1/2*I, x = 1.5, y = -1.5, T[v] = 1/2*3^(1/2)+1/2*I, u[0] = 1/2*3^(1/2)+1/2*I, v[0] = 1/2*3^(1/2)+1/2*I, j = 1, k = 3}

Result: .8660254040+.5000000000*I
Test Values: {v = 1/2*3^(1/2)+1/2*I, x = 1.5, y = -1.5, T[v] = 1/2*3^(1/2)+1/2*I, u[0] = 1/2*3^(1/2)+1/2*I, v[0] = 1/2*3^(1/2)+1/2*I, j = 2, k = 1}

... skip entries to safe data
Error
1.6.E49 βˆ₯ 𝐓 u Γ— 𝐓 v βˆ₯ = ( βˆ‚ ⁑ ( x , y ) βˆ‚ ⁑ ( u , v ) ) 2 + ( βˆ‚ ⁑ ( y , z ) βˆ‚ ⁑ ( u , v ) ) 2 + ( βˆ‚ ⁑ ( x , z ) βˆ‚ ⁑ ( u , v ) ) 2 norm subscript 𝐓 𝑒 subscript 𝐓 𝑣 superscript partial-derivative π‘₯ 𝑦 𝑒 𝑣 2 superscript partial-derivative 𝑦 𝑧 𝑒 𝑣 2 superscript partial-derivative π‘₯ 𝑧 𝑒 𝑣 2 {\displaystyle{\displaystyle\|\mathbf{T}_{u}\times\mathbf{T}_{v}\|=\sqrt{\left% (\frac{\partial(x,y)}{\partial(u,v)}\right)^{2}+\left(\frac{\partial(y,z)}{% \partial(u,v)}\right)^{2}+\left(\frac{\partial(x,z)}{\partial(u,v)}\right)^{2}% }}}
\|\mathbf{T}_{u}\times\mathbf{T}_{v}\| = \sqrt{\left(\pderiv{(x,y)}{(u,v)}\right)^{2}+\left(\pderiv{(y,z)}{(u,v)}\right)^{2}+\left(\pderiv{(x,z)}{(u,v)}\right)^{2}}

Error
Norm[Subscript[T, u] * Subscript[T, v]] == Sqrt[(((D[(x , y), {temp, 1}]/.temp-> (u , v))))^(2)+(((D[(y ,(x + y*I)), {temp, 1}]/.temp-> (u , v))))^(2)+(((D[(x ,(x + y*I)), {temp, 1}]/.temp-> (u , v))))^(2)]
Translation Error Translation Error - -
1.6.E50 βˆ₯ 𝐓 ΞΈ Γ— 𝐓 Ο• βˆ₯ = ρ 2 ⁒ | sin ⁑ ΞΈ | norm subscript 𝐓 πœƒ subscript 𝐓 italic-Ο• superscript 𝜌 2 πœƒ {\displaystyle{\displaystyle\|\mathbf{T}_{\theta}\times\mathbf{T}_{\phi}\|=% \rho^{2}\left|\sin\theta\right|}}
\|\mathbf{T}_{\theta}\times\mathbf{T}_{\phi}\| = \rho^{2}\abs{\sin@@{\theta}}

Error
Norm[Subscript[T, \[Theta]] * Subscript[T, \[Phi]]] == \[Rho]^(2)* Abs[Sin[\[Theta]]]
Translation Error Translation Error - -